2019
DOI: 10.1111/cdep.12344
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn About Aggression From What Adolescents Consider Important in Life? The Contribution of Values Theory to Aggression Research

Abstract: Values are abstract goals that serve as guiding principles in people's lives. Schwartz's theory (1992) offers a comprehensive framework to understand what motivates human behavior. It classifies people's broad motivations into a system of values organized in a circumplex structure. In this article, I explain how recent findings from studies of values can add to our knowledge of what motivates adolescents to behave aggressively. For example, during adolescence, values emphasizing caring for others and maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…There are four types of higher-order values, each representing a broad motivational goal: self-transcendence, openness-to-change, self-enhancement, and conservation ( Schwartz, 1992 , 1994 ). This values structure has been found in 70 countries (e.g., Schwartz and Rubel, 2005 ), and research has consistently demonstrated associations of the four value types with personality ( Parks-Leduc et al, 2015 ), attitudes ( Boer and Fischer, 2013 ), and behaviors ( Bardi and Schwartz, 2003 ; Benish-Weisman, 2015 , 2019 ).…”
Section: Introductionmentioning
confidence: 59%
“…There are four types of higher-order values, each representing a broad motivational goal: self-transcendence, openness-to-change, self-enhancement, and conservation ( Schwartz, 1992 , 1994 ). This values structure has been found in 70 countries (e.g., Schwartz and Rubel, 2005 ), and research has consistently demonstrated associations of the four value types with personality ( Parks-Leduc et al, 2015 ), attitudes ( Boer and Fischer, 2013 ), and behaviors ( Bardi and Schwartz, 2003 ; Benish-Weisman, 2015 , 2019 ).…”
Section: Introductionmentioning
confidence: 59%
“…Self-enhancement values are personal-focused and anxiety-avoidance, which emphasize the pursuit of self-interest by controlling others and resources or gaining social recognition and may increase aggression, which damages harmony relationships (Benish-Weisman, 2019 ). In contrast, self-transcendence values are social-focus and anxiety-free, which express a growth motivation and reflect care for others' well-being over self-interests and thus may increase prosociality, which helps to build and maintain relations.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Ungvary et al ( 2017 ) not only found that self-enhancement values positively correlated with aggression but also found that adolescents who high on self-enhancement and conservation values may have less aggression. Thus, such a person-centered approach helps to investigate the potential protective or destructive effect of one value on another (Benish-Weisman, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ample research has demonstrated the relations between values and behaviors (Roccas & Sagiv, 2017), and recent studies have examined the relations between values and aggression (for a review, see Benish‐Weisman, 2019). These studies suggest the importance adolescents attribute to high‐order values of self‐enhancement and self‐transcendence is associated with their aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐enhancement values express the motivation to gain dominance and control over people and resources (power); they also express the motivation for competence and personal success (achievement). The importance of power values increases in adolescence, possibly as a result of self‐differentiation, autonomy, and competence seeking (Daniel & Benish‐Weisman, 2019). Self‐enhancement values, particularly power, have been positively related to self‐reported violent behavior (Knafo, 2003; Knafo et al., 2008), traditional bullying and cyberbullying (Menesini et al., 2013), and peer‐nominated aggression (Benish‐Weisman, 2015) and negatively related to the expression of empathy with others (Myyry & Helkama, 2001).…”
Section: Introductionmentioning
confidence: 99%